(untitled) (Global Journal of Medical Research, 2021)
Background: Cervical cancer is the second commonest malignancy in women worldwide, and a leading cause of cancer-related death for women in Nigeria. Unfortunately, treatment for cervical cancer induces renalfunction injury due the nephrotoxicity of commonly used cytotoxic medications, as well as radiotherapy. Thus, this study seeks to evaluate the effect of radiotherapy on the renal function of cervical cancer patients. Objectives: 1) To examine if there will a positive of effect of radiotherapy on renal function in patients with cervical cancer after treatment. 2) To ascertain the statistical significance of the difference in renal function of cervical patients before and after treatment. Method: The study was an ex post facto research, used for retrospective evaluation of documented information on 220cervical cancer patients treated in the department of radiotherapy and oncology UDUTH, Sokoto. The study covered a five-year period, beginning from January, 2010 to December, 2015. Data was obtained from the patients#x2019; case notes using a semi-structured data extraction form. Percentage and analysis, independent t-test and chisquare statistics was used to determine the outcome of the findings.